Agricultural Communities’ Risk Assessment and the Effects of Climate Change: A Pathway Toward Green Productivity and Sustainable Development - Sohail, Muhammad Tayyab; Mustafa, Sohaib; Ali, Mazurina Mohd; Riaz, Sidra (Frontiers in Environmental Science, 2022)
The current study was carried out to assess agricultural communities' understanding of climate change, adaptation measures against climate change, and industrial wastewater irrigation and it is was important to check agricultural communities' understanding of climate change because the majority of the study area belongs to the farming and industry sector. This study was based on primary data collected through a survey in the study area. Results of present study showed that agricultural communities with sufficient resources and assets consider themselves to be safer and more capable of coping with the negative effects of climate change. Agricultural communities used different techniques to deal with impacts of climate change in present study area. The findings of this study about agricultural households' adaptation tactics are unique and will aid policymakers in assisting agricultural communities' in their day-to-day activities and farming practices, as well as in the implementation of proper monitoring and public policies to ensure integration and sustainability. This research is based on the sustainable livelihoods approach (SLA) that how livelihood assets support agricultural communities by combining household adoption/adaptation strategies and livelihood outcomes.